Semi open Innovation: an Approach to the Innovation Typology - Rocha, Andréia de Fátima Ribeiro; Santos, Isabel Cristina dos; Vieira, Almir Martins (Future Studies Research Journal: Trends and Strategies, 2018)
Purpose: This study aims to contribute to the Innovation Models debate from a new perspective on the innovation process, more frequently discussed in a range from closed to open innovation model. Coming into to the discussion in the recent years, called semi open innovation, this modality of innovation has been referenced as one that uses external knowledge, however considers that this knowledge is not a crucial element for the development of innovation. In this present study, semi-open innovation is characterized when the innovation process meets specific conditions of particular set of technologies and companies bounded by the local conditions. Design/Methodology/Approach: it refers to a qualitative study, supported by case studies. Findings: It was observed that the existence of a local Scientific and Technology Institute is a reason to define the location to produce, but did not find evidences of a large use of STI resources or with other local researchers for a product development. We could not clearly identify real open innovation model in practice. However, the proximity of a technological education and University of great national reputation, in addition to providing skilled labour, becomes a source of knowledge that should be used more frequently. Conclusions pointed out that there is a restricted support given by STI. The cases show that two firms practice an open innovation mode. In one case we conclude it refers to semi-open innovation practice.